2021
DOI: 10.2147/jpr.s299595
|View full text |Cite
|
Sign up to set email alerts
|

The Analgesic Effects of Thoracic Paravertebral Block versus Thoracic Epidural Anesthesia After Thoracoscopic Surgery: A Meta-Analysis

Abstract: Background To date, there is no definitive evidence for the analgesic effects and side effects of thoracic epidural anesthesia (TEA) versus thoracic paravertebral block (TPVB) after thoracoscopic surgery. In this study, we conducted a meta-analysis of published randomized clinical trials (RCTs) to analyze the analgesic effects of TEA versus TPVB after thoracoscopic surgery. Methods We systematically searched RCTs published by October 26, 2020, in PubMed, EMBASE, and Coc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…In recent years, due to the risks and limitations of thoracic epidural anesthesia (TEA), such as limited inclusion of patients using anticoagulants and the high rates of respiratory depression, hypotension and postoperative urinary retention associated with TEA [ 28 , 29 ], it has been gradually replaced by other techniques, such as ultrasound-guided PVB and ESPB. PVB has been used in clinical practice for more than 100 years, and its unilateral block features retain the sympathetic nerve function on the contralateral side, thereby greatly reducing the risk of hypotension, respiratory depression, and urinary retention [ 30 ]; moreover, a large number of studies have shown that the analgesic effect of PVB is comparable to TEA [ 8 , 31 ]. Therefore, an increasing number of hospitals recommend using PVB for postoperative analgesia for patients undergoing thoracic and breast surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, due to the risks and limitations of thoracic epidural anesthesia (TEA), such as limited inclusion of patients using anticoagulants and the high rates of respiratory depression, hypotension and postoperative urinary retention associated with TEA [ 28 , 29 ], it has been gradually replaced by other techniques, such as ultrasound-guided PVB and ESPB. PVB has been used in clinical practice for more than 100 years, and its unilateral block features retain the sympathetic nerve function on the contralateral side, thereby greatly reducing the risk of hypotension, respiratory depression, and urinary retention [ 30 ]; moreover, a large number of studies have shown that the analgesic effect of PVB is comparable to TEA [ 8 , 31 ]. Therefore, an increasing number of hospitals recommend using PVB for postoperative analgesia for patients undergoing thoracic and breast surgery.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, thoracic peripheral nerve block has gradually received attention and promotion with the cooperation of ultrasound technology, mainly including paravertebral block (PVB), erector spinae plane block (ESPB) and intercostal nerve block. Among them, PVB has been reported to have similarly effective analgesic effects as TEA, resulting in relatively fewer complications [ 8 , 9 ]. But PVB requires high technical proficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Risks associated with PVB include hypotension, urinary retention, hematoma, inadvertent intrathecal or epidural spread of the drug, and pneumothorax [ 8 ]. The unilateral nature of PVB results in preservation of sympathetic and respiratory function on the side of the body contralateral to the injection, which may account for the reduced frequency of hypotension and urinary retention associated with PVB as compared to TEA [ 9 ]. Evidence suggests PVB affects blood pressure and heart rate less significantly than other forms of regional anesthesia and is therefore the intervention of choice in patients with a history of cardiac disease [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies found no significant difference in pain relief provided between the two methods [ 2 , 7 , 8 ]. However, a retrospective case study published in 2021 by Liang and colleagues found that TEA provided statistically significant reduction of pain scores and amount of opioids used in the first 24 hours post-surgery when compared to PVB [ 9 ]. These findings are further supported by a prospective study published in 2020 by Yeap and colleagues which found TEA to be superior to PVB in patient pain control and reduction of opioid use over the first 72 hours following video-assisted thoracoscopic surgery [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation